2023
DOI: 10.3389/fmicb.2023.1018242
|View full text |Cite|
|
Sign up to set email alerts
|

A westernized diet changed the colonic bacterial composition and metabolite concentration in a dextran sulfate sodium pig model for ulcerative colitis

Abstract: IntroductionUlcerative colitis (UC) is characterized by chronic inflammation in the colonic epithelium and has a blurred etiology. A western diet and microbial dysbiosis in the colon were reported to play a role in UC development. In this study, we investigated the effect of a westernized diet, i.e., increasing fat and protein content by including ground beef, on the colonic bacterial composition in a dextran sulfate sodium (DexSS) challenged pig study.MethodsThe experiment was carried out in three complete bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 106 publications
0
3
0
Order By: Relevance
“…Diversity analysis and adonis analysis showed that the composition of gut bacteria in the HGR group was significantly different from the other two groups, specifically in terms of Desulfobacterota at the phylum level, and Rikenellaceae_RC9_gut_group , Ruminococcus , and Paeniclostridium at the genus level. Previous studies demonstrated that Desulfobacterota were mainly concentrated in the hindgut of animals and were significantly enriched in a wide range of diet-induced intestinal inflammation conditions in mice ( Panah et al, 2023 ; Ruan et al, 2023 ). They have also been suggested to be a marker of intestinal barrier damage ( Rao et al, 2021 ), largely due to the fact that Desulfobacterota lipopolysaccharides are severe inflammatory stimulants for the host ( Huang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Diversity analysis and adonis analysis showed that the composition of gut bacteria in the HGR group was significantly different from the other two groups, specifically in terms of Desulfobacterota at the phylum level, and Rikenellaceae_RC9_gut_group , Ruminococcus , and Paeniclostridium at the genus level. Previous studies demonstrated that Desulfobacterota were mainly concentrated in the hindgut of animals and were significantly enriched in a wide range of diet-induced intestinal inflammation conditions in mice ( Panah et al, 2023 ; Ruan et al, 2023 ). They have also been suggested to be a marker of intestinal barrier damage ( Rao et al, 2021 ), largely due to the fact that Desulfobacterota lipopolysaccharides are severe inflammatory stimulants for the host ( Huang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“… 49 Western dietary patterns, characterized by high consumption of fats and sugars and a low fiber intake, contribute to the development of IBD, because of the decreased abundance of SCFA-producing bacteria and the increased abundance of pathogens such as Helicobacter trogontum . 50 Although saturated fat is highly recognized a risk factor for IBD, O'Mahony et al 51 report that a lard-based high-fat diet demonstrates the potential to reduce DSS-induced colitis via inducing high level of the secondary bile acid lithocholic acid and activating the vitamin D pathway. Nevertheless, Khademi et al 52 support that there is no significant link between pro-inflammatory diets containing french fries, pizza, snacks, and red and processed meats with UC risk.…”
Section: Disease Pathogenesismentioning
confidence: 99%
“…The cause of UC is complex and not completely clear, and might be related to many factors like genetic, microbiota, immune system, stress, and diet [ 3 ]. Risk factors, including a Westernized diet characterized by a high intake of saturated fats and refined sugar, smoking, stress, and antibiotics can increase the incidence of UC [ 4 ]. Medications such as 5-aminosalicylic acids (sulfasalazine, mesalamine, balsalazide and olsalazine), corticosteroids (prednisone and budesonide), thiopurines, immunomodulators, and other biologics are typically used for the maintenance of UC remission [ 2 ].…”
Section: Introductionmentioning
confidence: 99%